O(A) professor(a) de matemática no contexto da inclusão escolar - Samira Zaidan (2001)
How has a mathematics teacher been working with all the changes, which have occurred at grade school? This is the question that incited this work. As a theoretical reference it was chosen the concept of experimental knowledge (FIORENTINI and others, 1998, 1999; TARDIF, 1991, 2000; BARTH, 1993). The methodology option used here was the one of observing and reflecting about mathematics teachers, who teach up to the eighth grade,working with teenagers. For a better understanding of teaching practices observations, the work makes salient the existence of a Pedagogical renewing movement in Brazil during 90s, which is about the discussions of having a school as a time/space place to grant the education for the pupils as something that goes beyond the acquisition of information and scientific knowledge, and the universality of the basic education. The society amplifies its vision of education and the functions of schools as ARROYO (2000), D´AMBRÓSIO (1996);FREIRE (1991, 1996, 2000). This research has pointed out the inclusion of popular classes into regular education as something essential, which brings out the necessity of dealing with a bigger social-economic and cultural diversity within the schools. The mathematics teachers have amplified their sight over education as a whole, and the role of mathematics itself has changed the teachers place inside the schools, as they realized their role not only as mathematics teachers but also as being engaged in the reality of the schools, and also in a pedagogical project. Among multiples knowledge being established in teachers practices, it is pointed out that the education has looked for establishing a relational mathematics, seeking a more meaningful learning process. This knowledge is related to others, as to other dimensions of life; and it suggests some signs in preparing the teachers for their role as educators.